2010
DOI: 10.1093/her/cyq017
|View full text |Cite
|
Sign up to set email alerts
|

A cognitive-behavioural pedometer-based group intervention on physical activity and sedentary behaviour in individuals with type 2 diabetes

Abstract: The purpose of this study was to investigate the benefits of a pedometer and a cognitive-behavioural group intervention for promoting physical activity (PA) in type 2 diabetes patients. We recruited 41 participants and randomized them into an intervention group (IG) (n = 20) and a control group (CG) (n = 21). The intervention consisted of five sessions within 12 weeks, a booster session after 22 weeks and a pedometer. Primary outcome was PA assessed by accelerometer (minutes per day) and pedometer (steps per d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
156
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(166 citation statements)
references
References 37 publications
9
156
0
1
Order By: Relevance
“…Earlier studies [21][22][23][24][25][26][27][28][29] found similar results concerning the behavioral effects of group counseling. Furthermore, some authors did not find effects on health outcomes after group counseling [22,25,29].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Earlier studies [21][22][23][24][25][26][27][28][29] found similar results concerning the behavioral effects of group counseling. Furthermore, some authors did not find effects on health outcomes after group counseling [22,25,29].…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, some authors did not find effects on health outcomes after group counseling [22,25,29]. Those three interventions had a similar duration as ours and focused on PA.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Most lifestyle intervention studies have focused on education programs (24), including advice on PA (25), diet (26), and both (19). An Italian study reported that behavioral changes are needed to achieve the goals of exercise training: in this study, lack of time and negative attitudes were the most common obstacles reported by patients (27).…”
Section: Introductionmentioning
confidence: 68%
“…18 Furthermore, in a previous intervention in the LMD, SBP ( -4.3 mmHg) and HDL-C (7.9 mg/dL) levels improved after a 6-month uncontrolled community-based walking intervention. 19 Conversely, a 6-month church-based weight loss intervention in the LMD found no clinically significant change in risk factors, although participants achieved weight loss.…”
Section: Figmentioning
confidence: 84%